EVALUATION OF CLINOPTILOLITE ZEOLITES FROM CAMAGÜEY FOR THE REMOVAL OF AMMONIUM IN POLLUTED WATERS - Sánchez Vargas, Héctor (2022)
The inadequate management of urban and agro-industrial waste has increased the presence of the ammonium ion in surface and groundwater worldwide, bringing with it the phenomenon of eutrophication and the loss of biological diversity, for which the design of systems is required. of alternative treatments for the elimination of this dangerous ion. The objective of the work was to evaluate the adsorption capacity of dissolved ammonium in contaminated water using the zeolite clinoptilolite from the San José del Chorrillo deposit in the Cuban province of Camagüey. Zeolites in their natural, incinerated and sodium states were evaluated, and thermodynamic and kinetic models were also fitted. Natural sodium zeolite has the highest adsorption capacity, which can reach values ​​close to 14 mg/g. The models that best fit the adsorption process studied are the Laugmuir thermodynamic model, with an R2 close to 0.99, and the pseudo second order kinetic model, with a fit error lower than the first order. It was concluded that this study provides relevant data for the correct design of a treatment system for water contaminated with ammonium.